2012
DOI: 10.1242/dev.066522
|View full text |Cite
|
Sign up to set email alerts
|

Midbrain-hindbrain boundary patterning and morphogenesis are regulated by diverse grainy head-like 2-dependent pathways

Abstract: SUMMARYThe isthmic organiser located at the midbrain-hindbrain boundary (MHB) is the crucial developmental signalling centre responsible for patterning mesencephalic and metencephalic regions of the vertebrate brain. Formation and maintenance of the MHB is characterised by a hierarchical program of gene expression initiated by fibroblast growth factor 8 (Fgf8), coupled with cellular morphogenesis, culminating in the formation of the tectal-isthmo-cerebellar structures. Here, we show in zebrafish that one ortho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 65 publications
3
52
0
Order By: Relevance
“…Grh is also downstream of erk signaling in Drosophila wound healing. In zebrafish, subphenotypic concentrations of grhl2b and fgf8 morpholino knockdown lead to MHB patterning defects (Dworkin et al ., ). These links to FGF signaling are consistent with the finding FGF is required for neuronal survival in the mouse forebrain (Paek et al ., ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Grh is also downstream of erk signaling in Drosophila wound healing. In zebrafish, subphenotypic concentrations of grhl2b and fgf8 morpholino knockdown lead to MHB patterning defects (Dworkin et al ., ). These links to FGF signaling are consistent with the finding FGF is required for neuronal survival in the mouse forebrain (Paek et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…Grhl2 has been liked to the control of cell proliferation in a number of different contexts. Morpholino knockdown of grhl1b in fish leads to increased apoptosis in the CNS (Dworkin et al, 2012). Grh also regulates neuroblast proliferation in Drosophila (Brody and Odenwald, 2000;Cenci and Gould, 2005;Maurange et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Although the results of our immunohistochemical and GRHL2 mRNA expression analyses clearly point towards a preferential expression of GRHL2 in epithelial tumours, for the first time evidence also for an expression of GRHL2 in tumours of non‐epithelial origin is provided. Developmental studies already revealed that GRHL2 represents a key regulator of neural patterning and morphogenesis . Grhl2 mutant mice among many developmental defects present with general defects in heart and embryonal neural tube formation .…”
Section: Discussionmentioning
confidence: 99%
“…been shown that distinct pathways govern the morphological and molecular features of the MHB downstream of the common transcription factor grainyhead-like 2 (Grhl2), with engrailed 2 acting downstream of Grhl2 to promote cell survival and formation of the molecular boundary (Dworkin et al, 2012). In addition to the co-repressive actions of Otx2 and Gbx2 at the boundary, Fgf8, Gbx2 and Notch signalling (Sunmonu et al, 2011;Tossell et al, 2011) promote cell sorting and, hence, lineage restriction at the boundary.…”
Section: The Cerebellar Anlage Sits Between Hox and Otx Domainsmentioning
confidence: 99%